2021
DOI: 10.1016/j.psj.2020.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of saponins and live coccidiosis vaccines: the influence of a quillaja and yucca combination on anticoccidial effects and performance results of coccidia-vaccinated broilers

Abstract: A series of studies was conducted to determine the effects of a quillaja and yucca (saponin) combination ( QY ) product on postvaccination oocyst production, development of coccidial immunity, and final bird performance of broilers administered live coccidiosis vaccines. In all, 3 groups of tests were carried out. Study 1 evaluated the effects of QY (0 and 250 ppm) on oocyst per gram of feces ( OPG ) following vaccination at day-of-age; OPG were measured from 5 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
(12 reference statements)
0
15
0
2
Order By: Relevance
“…Trial results indicated that at least part of this effect was associated with a lower level of coccidiosis in birds receiving QY. However, better coccidiosis control did not account for all the improvements recorded, and it was hypothesised that other intestinal effects may have been involved in these growth responses (Bafundo et al 2021). The current data showed that QY produced general improvements in the apparent intestinal uptake of dry matter, organic matter, fats and minerals and N retention.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Trial results indicated that at least part of this effect was associated with a lower level of coccidiosis in birds receiving QY. However, better coccidiosis control did not account for all the improvements recorded, and it was hypothesised that other intestinal effects may have been involved in these growth responses (Bafundo et al 2021). The current data showed that QY produced general improvements in the apparent intestinal uptake of dry matter, organic matter, fats and minerals and N retention.…”
Section: Discussionmentioning
confidence: 56%
“…In addition, each pen was sprayed with 1 × 10 5 Eimeria acervulina and 3.5 × 10 4 E. maxima sporulated oocysts per bird prior to the start of each test. As shown in Bafundo et al (2021), these procedures are known to induce a significant intestinal disease challenge characterised by moderate to severe coccidiosis, moderate NE and overall mortality two to three times greater than American industry standards. Evaluation of both coccidial and NE lesions at critical time points and total mortality at the end of the trial confirmed the highly pathogenic nature of these conditions.…”
Section: Morphometric Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in line with recently published data concerning the use of saponin-rich plants ( Quillaja.s ) by the Bafundo team and those published by Saeed et al ( Yucca.s ). ( 24 , 25 ). On the other hand, a recent study shows that saponin-rich plant supplementation ( Yucca.s ) does not have a significant compensation effect on the loss of performance of chickens infested by Eimeria ( 26 ); thus, contradicting obtained data from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…An example is a combination of quillaja and yucca that contain saponins and are often used to promote intestinal health and immunity in poultry ( Bafundo et al, 2020 ). In a series of studies they were shown, in addition to improving gut health, to have beneficial effects against infections with Eimeria species, necrotic enteritis, and improve the effectiveness of live coccidiosis vaccines ( Bafundo et al, 2021a , b ). Synergism has been claimed for a 1:1 mixture of the natural alkaloid berberine and amprolium ( Malik et al, 2016 ).…”
Section: Anticoccidial Drugs Used In Combinationsmentioning
confidence: 99%